The formation mechanism and effect of amorphous SiO2 on the corrosion behaviour of Fe-Cr-Si ODS alloy in LBE at 550 °C. (September 2021) - Xu, Zhiyuan; Song, Liangliang; Zhao, Yanyun; Liu, Shaojun
Highlights: The corrosion behaviour of the developed Fe-Cr-Si ODS in LBE at 550 °C was studied. The oxide scale/matrix interface features were investigated using the FIB and TEM. Amorphous SiO2 particles formed preferentially at the inner oxide layer, and delayed the growth of the outer magnetite layer. SiO2 promoted the formation of Cr-rich oxides and reduced the interface defects. Abstract: The corrosion behaviour of the newly developed Fe-Cr-Si oxide-dispersion-strengthened alloys in liquid lead–bismuth eutectic at 550 °C was microstructurally studied. The corrosion resistance was enhanced with increasing Si content, attributing to the preferred formation of amorphous SiO2 during the inward diffusion of oxygen. SiO2 promoted the formation of Cr-rich oxides that were uniformly distributed in the inner-oxide layer and matrix, thereby reducing the Fe and O diffusion coefficients and ultimately delaying the formation of the outer magnetite layer and the growth of the inner Cr-rich oxide layer while reducing interfacial defects.